New Vistas on Responsible Learning Analytics: A Data Feminist Perspective - Cerratto Pargman, Teresa; McGrath, Cormac; Viberg, Olga; Knight, Simon (Journal of Learning Analytics, 2023)
The focus of ethics in learning analytics (LA) frameworks and guidelines is predominantly on procedural elements of data management and accountability. Another, less represented focus is on the duty to act and LA as a moral practice. Data feminism as a critical theoretical approach to data science practices may offer LA research and practitioners a valuable lens through which to consider LA as a moral practice. This paper examines what data feminism can offer the LA community. It identifies critical questions for further developing and enabling a responsible stance in LA research and practice taking one particular case — algorithmic decision-making — as a point of departure.